A High-rate, Long Life, and Anti-self-discharge Aqueous N-doped Ti3C2/Zn Hybrid Capacitor. (March 2021) - Jin, Y.; Ao, H.; Qi, K.; Zhang, X.; Liu, M.; Zhou, T.; Wang, S.; Xia, G.; Zhu, Y.
Abstract: Two-dimensional transition metal carbides (nitrides) MXenes have excellent electrochemical properties and be hoped as a promising electrode material for supercapacitors. However, MXene nanosheets are prone to aggregate due to van der Waals interaction, which affect its electrochemical performance. In this study, nitrogen-doped Ti3 C2 (N-Ti3 C2 ), which hydrothermally prepared from MXene Ti3 C2, was assembled with metallic zinc to obtain a hybrid capacitor system in 1 M ZnSO4 aqueous electrolyte. In the voltage range of 0.05–1.2 V, the specific capacitance of this capacitor can reach 247.9 F g −1 (corresponding to an energy of 45.54 Wh kg −1 ). At high current density, it can quickly charge and discharge in 27 s, accompanied a high power output of 4093 W kg −1 and an energy of 30.99 Wh kg −1 . It presents an outstanding cycling stability with 88.34% capacity retention over 6000 cycles. The self-discharge rate in 240 h is only 1.24 mV h −1 . The high electrochemical performance mainly based on the introduction of nitrogen heteroatoms in cathode of N-Ti3 C2, which show the ion adsorption/desorption, and the deposition/exfoliation of Zn (Zn 2+ ) on the Zn anode to combine a hybrid capacitor. Highlights: A convenience and cheap preparation method to synthesis N-doped Ti3 C2 . The introduction of nitrogen heteroatoms improves the structural stability and electrochemical performance of the Ti3 C2 . The N-Ti3 C2 // ZnSO4 (aq) // Zn hybrid capacitor system has an outstanding electrochemical performance.